Incomplete Vogt-Koyanagi-Harada Disease and an Innocent Bystander: Unilateral Optic Disc Pit - Sefi k Can Ipek; Ziya Ayhan; Ali Osman Saatci (Journal of Clinical Research and Ophthalmology - Peertechz Publications, 2018)
We present a case with incomplete Vogt-Koyanagi Harada disease and coexistent unilateral optic disc pit. It is well-known that optic disc pits can present with intraretinal splitting and serous retinal detachment [1].